Design, analysis and fabricate of low speed water tunnel - Ahmad Zulfadhli, Mohd Khalid (2008)
This project goal was to construct a water tunnel that can used to do the experiment to analyze the hydrodynamic behavior of submerged bodies in flowing water. A new design was proposed to overcome the problem occurred from the project done at Wilkey University several years ago where it is can reproduce condition that can be decreased the reflection of water in tunnel. In order to design a water delivery system to the tunnel and produce an adequate flow, a 0.5hp pumps and 250 liters of reservoir were used to produce a 50L/min of velocity in the tunnel. Two experiments were conducted to test the functionality of the water tunnel and also the operation for the system. From the result obtained, there is no problem to deliver the water to the tunnel but it is still need some improvement to increase the water velocity in the tunnel